Cellular Immunity and Inflammatory Mediator Responses to Intense Exercise in Overweight Children and Adolescents. (1st April 2007) - McMurray, Robert G.; Zaldivar, Frank; Galassetti, Pietro; Larson, Jennifer; Eliakim, Alon; Nemet, Dan; Cooper, Dan M.
Abstract : Background: Obesity modifies inflammatory mediators, but little is known about how obesity modifies the inflammatory responses of exercising children. This study assessed the acute effect of exercise on inflammatory mediators in overweight children. Methods: Twenty-eight overweight (OW) youth (body mass index > 85%) and 30 normal-weight (NW) controls of the same proportions of age and gender performed 10 2-minute bouts of cycle ergometry exercise above the anaerobic threshold, with 1-minute rest intervals between bouts. Pre- and postexercise blood samples were collected for white blood cell subpopulation and inflammatory cytokines. Results: Baseline leukocyte populations were higher in OW youth ( p < .05). Exercise increased most leukocyte subtypes for both groups ( p < .05). Granulocytes remained elevated 2 hours postexercise ( p < .05) for both groups, whereas monocytes remained elevated 2 hours postexercise for the OW children. Natural killer (NK) cells dropped below baseline 2 hours postexercise. Exercise significantly decreased CD4 and CD8 cells, which remained depressed 2 hours postexercise in the OW children. Baseline levels of interleukin (IL)-6 were ≈64% higher in OW children ( p < .001). Exercise increased IL-6 in both groups ( p < .001), which further increased 2 hours postexercise ( p < .05). Tumor necrosis factor α, IL-1β, and IL-1 receptor antagonist did not change with exercise. Conclusions: Elevated baseline leukocyte subtypes and IL-6 levels in OW children suggest that childhood obesity is associated with a chronic low-grade inflammatory state. The acute inflammatory response to intense exercise appears to be similar between NW and OW children for most markers, but the depression of NK, CD4, and CD8 cells 2 hours postexercise suggests that an acute risk of mitogen-induced inflammation may exist in OW children after high-intensity exercise.